Plus Minus Pembelajaran Sejarah Jarak Jauh Media E-learning - Rina Karyani; Wardah Samiah (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
It is undeniable that the progress of the times demands progress in the field of education, many Indonesian schools have begun to apply ICT advances in several lessons. The situation that we are facing right now has become one of the factors, that the collaboration between tick and learning media must be carried out immediately. This article aims to examine the extent of distance learning readiness, starting from the understanding of distance itself, the method of distance learning that is applied by all schools in Indonesia, especially at the high school / vocational / equivalent level, and frequent problems faced when distance learning takes place. The writing of this article uses the phenomenological analysis approach method (a phenomenon that is slimming consciously), because the Covid-19 emergency does not require us to make direct observations of spaciousness.